2013
DOI: 10.2147/nss.s44736
|View full text |Cite
|
Sign up to set email alerts
|

Oral pressure therapy for treatment of obstructive sleep apnea: clinical feasibility

Abstract: PurposeThis feasibility study examined the initial-use safety and effectiveness of a new noninvasive oral pressure therapy (OPT) system developed to treat obstructive sleep apnea (OSA).MethodsThe OPT system consists of a console that connects with flexible tubing to a premanufactured polymer mouthpiece. Through the mouthpiece, a pump in the console creates oral vacuum intended to move the soft palate anteriorly to decrease obstruction of the airway during sleep. The mouthpiece was produced in ten different siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Through the mouthpiece, a pump in console creates oral vacuum in the oral cavity intended to move the soft palate anteriorly to decrease obstruction of the airway during sleep. 66 Farid-Moayer et al demonstrated in their study that in appropriately responsive patients, OPT can improve OSA without need for custom manufacture of an oral device. 66…”
Section: Oral Negative Pressure Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Through the mouthpiece, a pump in console creates oral vacuum in the oral cavity intended to move the soft palate anteriorly to decrease obstruction of the airway during sleep. 66 Farid-Moayer et al demonstrated in their study that in appropriately responsive patients, OPT can improve OSA without need for custom manufacture of an oral device. 66…”
Section: Oral Negative Pressure Therapymentioning
confidence: 99%
“…66 Farid-Moayer et al demonstrated in their study that in appropriately responsive patients, OPT can improve OSA without need for custom manufacture of an oral device. 66…”
Section: Oral Negative Pressure Therapymentioning
confidence: 99%
“…As an alternative to applying positive pressure to maintain the patency of the upper airway, this device generates negative oral pressure by drawing the tongue and soft palate in more anterior positions via a mouthpiece connected to a suction mechanism. An initial single-center feasibility study evaluating 76 subjects with mild, moderate, or severe OSA treated with negative oral pressure therapy demonstrated improvements in OSA severity and oxygen desaturation, and 38% of the patients achieved an AHI of not more than 10 events per hour [ 40 ]. Based on these initial data, a recent short-term prospective multicenter randomized controlled trial evaluated 63 middle-aged, predominantly obese subjects across the spectrum of OSA severity [ 41 ].…”
Section: Oral Negative Pressure Therapymentioning
confidence: 99%